Correction: Why is high persistence alone a major cause of concern?. Issue 5 (1st May 2019) - Cousins, Ian T.; Ng, Carla A.; Wang, Zhanyun; Scheringer, Martin
Abstract : Correction for 'Why is high persistence alone a major cause of concern?' by Ian T. Cousins et al., Environ. Sci.: Processes Impacts, 2019, DOI: ;10.1039/c8em00515j .